1993
DOI: 10.1073/pnas.90.7.2940
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic synthesis of acrylates in supercritical fluids: tuning enzyme activity by changing pressure.

Abstract: Supercritical fluids are a unique class of nonaqueous media in which biocatalytic reactions can occur. The physical properties ofsupercritical fluids, which include gas-like diffusivities and liquid-like densities, can be predictably controlled with changing pressure. This paper describes how adjustment ofpressure, with the subsequent predictable changes of the dielectric constant and Hildebrand solubility parameter for fluoroform, ethane, sulfur hexafluoride, and propane, can be used to manipulate the activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
3

Year Published

1995
1995
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(33 citation statements)
references
References 18 publications
2
28
0
3
Order By: Relevance
“…This extensive research into these systems has identified and elucidated the effects of many of the important variables, such as pressure (Miller et al, 1990(Miller et al, , 1991Erickson et al, 1990;Ikushima et al, 1993). Reaction rates in SC CO, and in organic solvents (typically hexane) have been compared (Martins et al, 1991;Bolz et al, 1991;Marty et al, 1990Marty et al, , 1992aKamat et al, 1992Kamat et al, , 1993Chi et al, 1988;Pasta et al, 1989). Kinetics parameters and reaction mechanisms have been reported (Miller et al, 1991;Bolz et al, 1991;Marty et al, 1992b;Dumont et al, 1992).…”
Section: Heterogeneous Catalysis and Heterogeneous Reactionsmentioning
confidence: 95%
See 4 more Smart Citations
“…This extensive research into these systems has identified and elucidated the effects of many of the important variables, such as pressure (Miller et al, 1990(Miller et al, , 1991Erickson et al, 1990;Ikushima et al, 1993). Reaction rates in SC CO, and in organic solvents (typically hexane) have been compared (Martins et al, 1991;Bolz et al, 1991;Marty et al, 1990Marty et al, , 1992aKamat et al, 1992Kamat et al, , 1993Chi et al, 1988;Pasta et al, 1989). Kinetics parameters and reaction mechanisms have been reported (Miller et al, 1991;Bolz et al, 1991;Marty et al, 1992b;Dumont et al, 1992).…”
Section: Heterogeneous Catalysis and Heterogeneous Reactionsmentioning
confidence: 95%
“…SC CO,, either pure or with a cosolvent, has been employed as the SCF solvent in nearly all investigations. The few exceptions are Hammond et al (1985) using fluoroform, and work at the University of Pittsburgh (Kamat et al, 1992(Kamat et al, , 1993) that employed SC ethane, ethylene, SF,, and CHF,. Several different enzymes have been shown to maintain their activity after exposure to SC CO,, pure and with added water and ethanol (Taniguchi et al, 1987).…”
Section: Heterogeneous Catalysis and Heterogeneous Reactionsmentioning
confidence: 98%
See 3 more Smart Citations